Scalable Electrocatalytic Urea Wastewater Treatment Coupled with Hydrogen Production by Regulating Adsorption Behavior of Urea Molecule - Chunming Yang; Huijuan Pang; Xiang Li; Xueyan Zheng; Tingting Wei; Xu Ma; Qi Wang; Chuantao Wang; Danjun Wang; Bin Xu (Nano-Micro Letters)
Highlights The heterogeneous interface of NiO/Co3O4 was constructed for regulating adsorption behavior of urea functional groups. The regulation mechanism of urea molecular adsorption behavior was verified by temperature-programmed desorption experiments and density functional theory calculations. Efficient and scalable electrocatalytic urea wastewater treatment coupled with hydrogen production was realized in anion exchange membrane water electrolyzer AEMWE, which can continuously treat urea wastewater at an initial current density of 600 mA cm-2, with about 53% in average urea treatment efficiency.